"Covid-working": what to keep and what to leave? Evidence from an Italian company. Issue 2 (25th June 2021) - Tagliaro, Chiara; Migliore, Alessandra
Abstract : Purpose: This paper aims to explore the extent to which Covid-19 has challenged work habits and outcomes. The authors argue that after the lockdown period workers have been experiencing a new work mode called "Covid-working". The aim is to provide a first interpretation of this phaenomenon and elaborate on future real estate strategies and workplace policies based on this experience. Design/methodology/approach: Using survey data, this research analyses Covid-working in a large-sized company in Italy. The survey was answered by 90 employees and addresses three domains: locations of work; a comparison between work-from-home (WFH) and work from the office; and outcomes of Covid-working vs office-working. Findings: With Covid-working, the workers of the case company drastically changed their traditional work from the office approach to pure WFH. While this abrupt switch might generate difficulties in adaptation, this working practice was generally appreciated by this company's workers. Positive and negative outcomes of Covid-working confirm previous studies on remote working. Recommendations on multi-location of work, new value for the headquarters and diversity empowerment open up avenues for future real estate strategies. Originality/value: Observations on Covid-working are still limited and mainly appear on grey literature, due to the newness of this phaenomenon. Empirical studies such as the proposed one can increase companies' awareness of the positive and negative outcomes of this experience and support their future workplace strategies.